Beyond intrinsic and extrinsic motivation: A meta-analysis on self-determination theory’s multidimensional conceptualization of work motivation - Van den Broeck, A.; Howard, J.L.; Van Vaerenbergh, Y.; Leroy, H.; Gagné, Marylène (SAGE PUBLICATIONS INC, 2021)
This meta-analysis aims to shed light on the added value of the complex multidimensional view on motivation of Self-determination theory (SDT). We assess the unique and incremental validity of each of SDT’s types of motivation in predicting organizational behavior, and examine SDT’s core proposition that increasing self-determined types of motivation should have increasingly positive outcomes. Meta-analytic findings (124 samples) support SDT, but also adds precision to its predictions: Intrinsic motivation is the most important type of motivation for employee well-being, attitudes and behavior, yet identified regulation is more powerful in predicting performance and organizational citizenship behavior. Furthermore, introjection has both positive and negative consequences, while external regulation has limited associations with employee behavior and has well-being costs. Amotivation only has negative consequences. We address conceptual and methodological implications arising from this research and exemplify how these results may inform and clarify lingering issues in the literature on employee motivation.